Evaluation of Kappa Index as a Tool in the Diagnosis of Multiple Sclerosis: Implementation in Routine Screening Procedure - Sanz Diaz, Carmen Teresa; de las Heras Flórez, Silvia; Carretero Perez, Mercedes; Hernández Pérez, Miguel Ángel; Martín García, Vicente (Frontiers in Neurology, 2021)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system. Previous studies have shown that cerebrospinal fluid (CSF) kappa free light chains (K-FLCs) may have a role in MS diagnosis. In this regard, the kappa index (K-Index) has demonstrated higher sensitivity, and slightly lower specificity than oligoclonal bands (OCBs), the gold standard for the detection of intrathecal immunoglobulin synthesis, a feature of MS. Here, we evaluated the performance of the K-Index (K-Index = CSF/serum K-FLC divided by CSF/serum albumin) for the differential diagnosis of MS in a cohort of patients with suspected MS. K-FLCs were quantitatively measured in parallel serum and CSF samples by turbidimetry (Freelite Mx reagent on an Optilite system, The Binding Site Group Ltd). From 160 (63.4%) of a total of 252 patients who had K-FLC in CSF <0.03 mg/dl, below the sensitivity limit of the technique, only one had a diagnosis of MS. However, the absence of OCB in this same patient suggested no synthesis of intrathecal immunoglobulin. Globally, MS patients presented significantly higher K-Index levels than patients without an MS diagnosis (66.96 vs. 0.025, respectively; p < 0.0001). In agreement, patients with positive OCB testing also exhibited higher K-Index levels than patients negative for OCB (65.02 vs. 0.024, respectively; p < 0.0001). An optimal K-Index cutoff of 3.045 was defined by receiver operating characteristic (ROC) analysis for screening suspected MS, achieving a higher diagnostic sensitivity and slightly lower specificity than OCB (Sens. 0.9778 and Spec. 0.8629 vs. Sens. 0.8889 and Spec. 0.9086, respectively). A previously reported K-Index cutoff of 6.6 also showed good diagnostic performance (Sens. 0.9333; Spec. 0.8731), validating its power as a diagnostic biomarker for MS. Finally, a time- and cost-effective algorithm for MS screening is proposed that would offer an initial rapid evaluation of the intrathecal immunoglobulin synthesis through the K-FLC in CSF and K-Index analysis, followed by reflexing OCB testing that may be ordered more selectively.